Thermal Behavior of Hollow and Solid Steel Beams with Different Boundary Conditions - Daud, Harbi A.; Daud, Sultan A.; Al-Azzawi, Adel A. (Computer Assisted Methods in Engineering and Science, 2021)
The thermal behavior of hollow steel structural members due to the temperature increase has not been investigated and discussed in many design codes. This work presents a study of the hollow and solid steel beams’ carrying capacity under elevated temperatures. The material properties of such beams decline under the temperature expected to increase the moments on the beams. The finite difference technique is selected first to analyze the problem. The solved problems cover beams under concentrated point load levels with different end conditions such as cantilever, pin roller, and both ends fixed. The beam response (deflection, bending moment, and normal force) is examined. The finite element analysis was conducted using the DIANA FEA software to study the same problem incorporating material and geometric nonlinearities. It was found that both finite difference and finite element analysis solved the problem accurately when the temperature was under 500°C. It was also found that when the temperature was applied to the beam bottom face the deflection was smaller than when the temperature was applied to the side faces only and the whole section.